DIURNAL DEPENDENCE OF THE FREQUENCY OF OCCURRENCE OF TRAVELING IONOSPHERIC DISTURBANCES OVER ALMATY - Yakovets, A.F.; Jahanshir, A.; Gordienko, G.I.; Zhumabayev, B.T.; Litvinov, Yu.G. (Academic Scientific Journal of Computer Science, 2020)
We studied the diurnal dependence of the frequency of occurrence of large-scale traveling ionospheric disturbances (LSTID’s) at mid-latitudes, which are a manifestation of atmospheric gravitaty waves (AGWs) generated in polar regions during geomagnetic disturbances. A significant amount of vertical sounding data of the ionosphere obtained at the Institute of the Ionosphere (Almaty 76 ° 55’E, 43 ° 15’N) in 2000-2007 was analyzed on a digital PARUS ionosonde connected to a computer designed to collect, store and process ionograms in digital form. Further processing included the calculation of the altitude distributions of electron density (N (h) profiles) by the Titeridge method and deriving from them variations of a number of F-region parameters (electron density at fixed heights Nh(t); density at the maximum of the layer NmF (t) ; the heights of the maximum of the layer NmF(t), etc.). The ionozonde provided a readout accuracy of h ’(t) 2.5 km and a readout accuracy of foF 0.05 MHz. It was shown that from session to session the number of waves observed during the night changed. In constructing the duirnal dependence of the frequency of occurrence of traveling ionospheric disturbances, all waves were taken into account. A diurnal dependence of the frequency of occurrence of traveling ionospheric disturbances over Almaty was constructed from the measurement data. For this, a visual control of the behavior of a number of parameters of the F-region was carried out, identification of the LSTID’s, determination of the time of their onset and duration. It is shown that the predominant beginning of the development of the LSTID’s is close to the moment of local midnight. 87% of traveling ionospheric disturbances were observed in the interval 20:00-04:00 LT. The distribution of the frequency of occurrence of the LSTID’s in the time of day coincides with the dependence of the substorm frequency on world time, explained on the basis of diurnal variations in the angle of inclination of the Earth’s magnetic axis to the Sun-Earth line. Ion drag and the dependence of the level of auroral activity, and, consequently, the intensity of the generation of LSTID’s, on world time determines that the most favorable conditions for the distribution of LSTID’s are created over Almaty at night.